Analisa Perbedaan Pandangan Antar Guru Tentang Kejujuran dan Kebohongan di SDN 02 Duhiadaa - Muh. Wahyuddin S. Adam; Erlin Lalu; Suci Tino; Nur Azizah (STIKes Ibnu Sina Ajibarang, 2025)
The research aims to analyze and examine differences in views between class IV, V and VI homeroom teachers regarding honesty and lies at SDN 02 Duhiadaa. This research uses a qualitative approach with a field research type of research. The data collection methods used in this research include in-depth interview methods to gain an understanding of a phenomenon or problem that is attracting attention in the school environment obtained from research information. The results of the research show that there are differences in views between teachers regarding their opinions about honesty and lies as well as strategies for forming an honest character but still caring about others.